DEFORMATION HISTORY AND CORRELATION OF PAIKON AND TZENA TERRANES (AXIOS ZONE, CENTRAL MACEDONIA, GREECE) - Katrivanos, E.; Kilias, A.; Mountrakis, D. (Bulletin of the Geological Society of Greece, 2016)
Paikon and Tzena terranes are situated in the centre part of Axios zone, between Almopia and Paionia ophiolitic belts. Tectonostratigraphic data reveal that both have been affected by the same polyphase deformation and metamorphism, as well that they have the same lithostratigraphic column. The first deformation phase took place during the Middle to Late Jurassic and is associated with ophiolite obduction, nappe- stacking, terrane accretion and crustal thickening (D1). Metamorphism does not exceed greenschist facies (M1). Relict HP-LT metamorphic assemblages predating M1 metamorphism are possibly developed during subduction processes and overloading of the obducted ophiolites on the continental margin, characterized the initial stages of deformation. Compressional tectonics and intense thrusting with the same kinematics continued in Lower Cretaceous time, affected all pre-Upper Cretaceous units and the obducted ophiolites (D2). This phase is associated with low-greenschist metamorphism (M2). The first main extensional event occurs in the Late Cretaceous, related to basin formation and sedimentation (D3). During Paleocene to Eocene, D4 intense imbrication of all tectonic units towards mainly SW takes place again. Nappes collapse and finally crustal exhumation taken place during Oligocene to Miocene, associated with low - angle normal faults, with a main top to the SW sense of movement (D5). In Miocene to recent times, high - angle normal and strike-slip faults are formed in an extensional to transtensional strain regime (D6), associated with Neogene to Quaternary basin formation and terrane dispersion. The basement rocks of both terranes are of Pelagonian origin, exhumed as a multiple tectonic window.